2016
DOI: 10.1097/ccm.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Antimicrobial Treatment for Bacteremia in Canadian Critically Ill Patients*

Abstract: Critically ill patients who have bacteremia typically receive long courses of antimicrobials. Most patient/pathogen characteristics are not associated with treatment duration; survivor bias precludes a valid assessment of the association between treatment duration and survival. A definitive randomized controlled trial is needed to compare shorter versus longer antimicrobial treatment in patients who have bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…While insufficient length of treatment could result in recurrent infection, prolonged duration of treatment is associated with adverse drug events, higher costs, and increased prevalence of drug-resistant bacteria. 28 Highlighting this point, Daneman et al’s 29 retrospective cohort study of bacteremic ICU patients to determine pathogen and patient-related factors associated with prolonged duration of antimicrobial therapy found that most patient or pathogen characteristics were not associated with treatment duration and that survival bias precluded a valid assessment of the association between duration and survival. In our study, duration of antibiotic treatment was based on clinical response to treatment, and also influenced by operative interventions such as excision and grafting, which may have served to lengthen duration of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…While insufficient length of treatment could result in recurrent infection, prolonged duration of treatment is associated with adverse drug events, higher costs, and increased prevalence of drug-resistant bacteria. 28 Highlighting this point, Daneman et al’s 29 retrospective cohort study of bacteremic ICU patients to determine pathogen and patient-related factors associated with prolonged duration of antimicrobial therapy found that most patient or pathogen characteristics were not associated with treatment duration and that survival bias precluded a valid assessment of the association between duration and survival. In our study, duration of antibiotic treatment was based on clinical response to treatment, and also influenced by operative interventions such as excision and grafting, which may have served to lengthen duration of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8 The participating sites were located within tertiary care teaching hospitals and represented 6 provinces and 10 cities (Appendix 1, available at www.cmajopen.ca/ content/4/4/E569/suppl/DC1). Patients who had a blood culture that grew a pathogenic organism during their ICU stay were eligible for inclusion in the study.…”
Section: Study Sites and Patientsmentioning
confidence: 99%
“…The primary objective of the Bacteremia Antibiotic Length Actually Needed for Clinical Effectiveness study 8 was to study duration of antibiotic treatment for bacteremia without deepseated infection, and thus some infections were excluded (endocarditis, osteomyelitis, septic arthritis, undrained abscess and unremoved prosthetic material); however, these represented a small minority. In addition, the use of routine microbiological testing data rather than data expressly collected for the purpose of resistance surveillance means that not all organisms were tested for susceptibility to all potentially relevant agents and that there may have been variability in susceptibility testing methods across ICU/hospital sites.…”
Section: Limitationsmentioning
confidence: 99%
“…In the study by Danemen et al (1), Staphylococcus aureus was the second most pathogen identified accounting for 12% of cases. Despite guidelines recommending at least 14 days of therapy, SAB was not associated with a longer duration of therapy.…”
mentioning
confidence: 97%
“…In this issue of Critical Care Medicine, Daneman et al (1) have explored the issue of treating bacteremia in the ICU with the hopes of answering this question. They conducted a large, multicenter retrospective study of 1,202 Canadian ICU patients with bacteremia excluding anyone with an infection who required a prolonged antibiotic course as per established infectious disease (ID) guidelines (endocarditis, osteomyelitis, etc.).…”
mentioning
confidence: 98%